Information security awareness and training program study on Wahda Bank-Libya - Abubaker Essid Abuhtera, 1966-, author; Norbik Bashah Idris, supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2014